Similarity solution for MHD nanofluid flow with heat generation in the presence of radiation and chemical reaction effects - Palani, G.; Arutchelvi, A. (Zielona Góra: Uniwersytet Zielonogórski)
An analysis has been carried out to study the two-dimensional free convective boundary layer MHD nanofluid flow past an inclined plate with heat generation, chemical reaction and radiation effects under convective boundary conditions. The partial differential equations describing the flow are coupled nonlinear. They have been reduced to nonlinear ordinary differential equations by utilizing a similarity transformation, which is then solved numerically with the aid of the Runge-Kutta-based shooting technique.
Keywords: free convection; nanofluid; viscous dissipation; moving inclined plate